Retroperitoneal malignant triton tumor in an infant: a case report and literature review - Hou, Zhibin (Transl Pediatr, 2020)
Malignant triton tumor (MTT) is a rare subtype of malignant peripheral nerve sheath tumor (MPNST) with rhabdomyoblastic differentiation. MTTs are solid tumors commonly located in the head, neck, extremities, and trunk. The presence of this tumor in an infant’s retroperitoneum is extremely rare, and prompted the authors to report this case with reference to existing literature.